Knowledge management for corporate social responsibility - Martín de Castro, Gregorio, 1972-; González-Masip, Jaime Juan, 1977- (Advances in business strategy and competitive advantage., 2021)
"This book explores the theoretical and practical aspects of linking firm profitability, social development, and natural environment in respect to business management practices"--